Measurement of Seebeck Coefficient at Cryogenic Temperature Based on Thermoelectric Module Experiments - Liu Zhibo; Li Jiamei; Wang Shixue; Zhu Yu (Zhileng xuebao)
Thermoelectric generators (TEG) are one way to utilize the cold energy of LNG. Inadequate research on the Seebeck coefficient (α) of thermoelectric materials at cryogenic temperatures has hindered the design of TEG at cryogenic temperatures. Consequently, this paper proposes a method to measure α of the thermoelectric material, Bi2Te3, at cryogenic temperatures using a TEG module experiment, which measures α of thermoelectric materials in the temperature range of 90 K to 180 K. The results showed that α of Bi2Te3 decreased with decreasing temperature. When the temperature decreased from 180 K to 90 K, α decreased from 124.6 μV/K to 49.3 μV/K, which is a quadratic function of temperature.